Incidence of Typhoid Fever and the Validity of the Widal Test in Some Districts in Iraq - Mousa A. Shubbar; Shakir M. Zighar (Al-Anbar Medical Journal)
Background: Typhoid fever is a serious infectious disease. In Iraq, the disease has a public health burden because it’s endemicity and there is an overestimation of the cases because the diagnosis almost depends on the Widal test. Objectives: The study aimed to determine the occurrence of typhoid fever in four sentinel sites in Iraq and to assess Widal test sensitivity and specificity. Materials and Methods: This cross-sectional observational study conducted in four districts in Iraq which has a population ranging from 170 000 to 431 000. A consecutive sample of (757) patients attended the outpatient or admitted to hospitals. Any Widal positive case, probable typhoid case and suspected typhoid case were included in the study. A questionnaire including demographic, clinical, laboratory and exposure data was filled for each suspected case. Confirmation of the diagnosis of typhoid fever was done by serological examination and culture (blood, urine or feces) for each patient included in the study.  Results: The occurrence of typhoid fever (per 100 000 population) was 34, 9.4, 3.5, 0 in Al-Haweeja, Al-Hay, Al-Majar, and North Najaf districts respectively and this occurrence was lower in three study districts when compared with the same period of 2010 and 2011. The mean of the age of cases was 25.8 years ±16.03 and the male to female ratio of confirmed cases was 0.7:1. Also, this study showed that the sensitivity of the Widal test was 16.7% and the specificity was 36.2% when compared with culture results. Conclusions: The incidence rate of typhoid fever was low in the four selected sites except for the Al-Haweeja district. The sensitivity and specificity of the Widal test were low.